Entre lo público y lo gubernamental. Caso ecuador tv. - Estrada Japón, Anais Alejandra (2014)
The communication between the public and the governmental is a topic of study and discussion in the field work of Ecuador TV. In this final work of grade the public communication, television, public opinion and the journalism categories are development to understand the public service in the television communication medium. When Rafael Correa got the Ecuador´s presidency, the communication started to give transcendental turns. Ecuador TV was in the 2007 with the finality to fragments the monopolies of the mass media that they have led more of fifty years in the Ecuadorian society. Considerate as the first Ecuador´s public channel, ECTV started with the objective serving to citizenship and providing educational and cultural contents.